Kesantunan Berbahasa Prabowo Subianto pada Closing Statement Debat Capres 2024 - Moon, Yuliana Jetia; Lisnawati Guntar, Elsita; Ungkang, Marcelus (Humanis; Vol 28 No 3 (2024), 2024)
Language politeness is one of the crucial issues, especially by public figures in public spaces. This is because he is a role model for the general public. Moreover, a public figure who wants to become the number one person in Indonesia. This research examines language politeness from the perspective of Leech's politeness maxims. The purpose of this study is to describe the language politeness practiced by Prabowo Subianto in the closing statement of the 2024 presidential candidate debate. The type of this research is qualitative descriptive method. The data collection method uses tapping, listening, and recording techniques. Based on the data, out of 25 sentences in the closing statement, 20 or 80% of the identified data fulfill the principles of politeness. While 20% are neutral. Based on the main ideas, out of 10 main ideas, there are 8 or 80% of them are identified as polite speech, while 2 or 20% of the main ideas are neutral. Based on Leech's maxims of politeness, there are six forms of politeness shown in the speech, namely tact maxim, generosity maxim , approbation maxim, modesty maxim, agreement maxim, sympath maxim .